SAFETY AND EFFICACY OF MONOPOLAR TRANSURETHRAL RESECTION OF PROSTATE IN LABORATORY PARAMETERS (Indonesian Urological Association, 2022)
Objective: This study aims to assess the safety and effectiveness of transurethral resection of prostate using preoperative and postoperative laboratory parameters. Material & Methods: This was a retrospective study of all patients treated with transurethral resection of prostate at Karawang Hospital from January – August 2018. The laboratory parameters are measured in the preoperative and postoperative period, including haemoglobin, leucocyte, and electrolyte. The outcomes of the study were the comparison of laboratory parameters before and after monopolar transurethral resection of prostate. Results: A total of 142 patients were enrolled in this retrospective study. The mean age was 68 years. Transurethral resection of prostate was performed in all patients. The mean of preoperative level of haemoglobin was higher compared to postoperative level (13.21 gr/dL vs 12.79 gr/dL; p = 0.000). The mean preoperative level of leucocyte was higher during postoperative time compared to preoperative time (13.450 vs 7503.52 p = 0.000). The sodium level was lower postoperative than preoperative ( 137.76 vs 139.39; p = 0.000 ). The potassium level was higher preoperative than in postoperative (4.12 vs 4.02, p = 0.000 ). The logistic regression was performed and shows no significant association between prostate resected weight and length of surgery compared to laboratory parameters. There was no patient who needed blood transfusion or having electrolyte derangement. Conclusion: Based on laboratory parameters, monopolar transurethral resection of prostate is safe and effective in the treatment of benign prostate hyperplasia.